Effect of Load Cooling on the Performance of Steam Power Plant Condensers - Adri, Junil; Arwizet, Arwizet; Ariyanto, Dedi (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2024)
This study analyzes the impact of cooling load on condenser performance in the Steam Power Plant. The condenser, as a heat exchanger, plays a critical role in condensing steam from the turbine back into liquid form, thus maintaining the continuous cycle of the steam power system. Survey-based research was conducted, with data collected on steam and cooling water temperatures at various stages. The steam inlet and outlet temperatures were recorded at 514°C and 465°C, respectively, with cooling water entering at 32.9°C and exiting at 38.9°C at a flow rate of 100 m³/h. Using the Log Mean Temperature Difference method, initial and final temperature differences were calculated at 453°C and 465°C. Results suggest that tube fouling or leakage contributes to declining condenser efficiency, which can significantly reduce power plant performance. This study highlights the importance of regular maintenance and monitoring of condenser units to optimize thermal efficiency and power generation output.